Análisis del cambio de coberturas naturales producida por la explotación a cielo abierto en canteras de magnesita en Bolívar - Valle del Cauca (2022)
This paper presents the changes in the soil during the years 2015, 2018 and 2021 that have generated the extraction of Magnesite in the Municipality of Bolívar (Cauca Valley). The obtained results demonstrate the transformation of coverages as they are: Vegetal Layer, Mining, Crops and Population. During this period it was observed that the most significant changes in the coverage are in the plant layers and mining. Changes in land cover and land use are determined by anthropic activities, which are responsible for changes in land cover and land use.